Ganoderma triterpenoids attenuate tumour angiogenesis in lung cancer tumour-bearing nude mice - Wei Liu; Ruiying Yuan; Aihua Hou; Song Tan; Xin Liu; Pengcheng Tan; Xiaoming Huang; Jinguo Wang (Taylor & Francis Group, 2020)
Context Ganoderma lucidum (Leyss. ex Fr.) Karst. (Polyporaceae) triterpenoids (GLTs), the main components and bioactive metabolites of G. lucidum, have antitumour activity. Objective We investigated the effects of GLTs in lung cancer tumour-bearing nude mice and their potential mechanism. Materials and methods Forty BALB/c nude mice were randomly divided into four groups: saline control, GLT (1 g/kg/day), gefitinib (GEF, 15 mg/kg/day), and GLT (1 g/kg/day) + GEF (15 mg/kg/day) for 14 days. Cell viability was conducted using the Cell Counting Kit-8 assay. The tumour volume, inhibition rate, histopathological, microvessel density (MVD), mRNAs, and proteins were determined. Results GLTs inhibited the cell viability of A549 cells with an IC50 value of 14.38 ± 0.29 mg/L, while the IC50 value of GEF was 10.26 ± 0.47 μmol/L. The tumour inhibition rate in the GLT + GEF group (51.54%) was significantly decreased relative to the saline control... group (p < 0.05). The MVD in the GLT + GEF group (2.9 ± 0.7) was significantly decreased than that in the saline control group (12.8 ± 1.4, p < 0.05). The angiostatin, endostatin, and Bax protein expression in the GLT, GEF, and GLT + GEF groups were significantly increased compared to those in the saline control group, while the VEGFR2 and Bcl-2 protein expression were decreased. Discussion and conclusions Our study provided evidence that GLT and GEF combination therapy may be a promising candidate for the treatment of lung cancer and as an experimental basis for clinical treatment.